2020
DOI: 10.1093/infdis/jiaa748
|View full text |Cite
|
Sign up to set email alerts
|

Interkingdom Communication and Regulation of Mucosal Immunity by the Microbiome

Abstract: Intercellular communication and environmental sensing are most often mediated through ligand-receptor binding and signaling. This is true for both host cells and microbial cells. The ligands can be proteins (cytokines, growth factors and peptides), modified lipids, nucleic acid derivatives and small molecules generated from metabolic pathways. These latter non-protein metabolites play a much greater role in the overall function of mucosal immunity than previously recognized and the list of potential immunomodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Recently, Rashidi and colleagues explored this interaction and identified that the microbial genera, Blautia , was critical in dictating the integrity of the intestinal mucosa, proposing a model of microbe-to-mucosa communication [44]. Certainly, microbes have the capacity to influence the mucosa, particularly via their ability to produce beneficial metabolites such as short chain fatty acids [45]. These compounds are a major energy source for colonocytes, promoting epithelial proliferation and regeneration, whilst also promoting barrier integrity via their influence on tight junction assembly.…”
Section: Mucosal-microbial Cross Talkmentioning
confidence: 99%
“…Recently, Rashidi and colleagues explored this interaction and identified that the microbial genera, Blautia , was critical in dictating the integrity of the intestinal mucosa, proposing a model of microbe-to-mucosa communication [44]. Certainly, microbes have the capacity to influence the mucosa, particularly via their ability to produce beneficial metabolites such as short chain fatty acids [45]. These compounds are a major energy source for colonocytes, promoting epithelial proliferation and regeneration, whilst also promoting barrier integrity via their influence on tight junction assembly.…”
Section: Mucosal-microbial Cross Talkmentioning
confidence: 99%
“…It is an oxylipin, a product of the metabolism of linoleic acid, a type of omega-6 fatty acid, formed through mono- or dioxygenase action. Gut bacteria, such as Enterococcus faecalis and Bifidobacterium spp., encode epoxide hydrolase enzymes capable of generating 12,13-diHOME [ 50 ]. This compound can act on dendritic cells, promoting a Th2-type inflammatory response, with its elevation being related to the development of allergic processes.…”
Section: Functional Products Of the Intestinal Microbiotamentioning
confidence: 99%
“…TJs comprise junctional adhesion molecules, claudins, occludins, and zonula occludens proteins. Some microbial metabolites can modulate the expression of TJs, for instance, SCFAs, prostaglandins, uric acid, and histamine [ 21 , 28 , 29 ].…”
Section: Microbiome and Mucosal Immunitymentioning
confidence: 99%